La visión del terrorismo en Las cloacas del paraíso de Jorge Díaz - Werman, Anna (Romanica Silesiana)
The present article outlines the problem of terrorism in The Sewers of Paradise by Jorge Diaz. Moving it to the current times, the play uses the Biblical myth of Cain and Abel, however, with a completely changed original meaning. The world presented in the play is full of absurd situations highlighting an individual’s incomprehension of the events that shape today’s socio-political scene. Díaz questions the ethics of the current world, emphasizing the following problems: the religious intolerance, authority abuse, opportunist manipulation, xenophobia, discrimination of women, conformism and solitude of the individual lost in a cruel and hostile universe. Generally, the work investigates the concept of terrorism and shows its complexity. The model of the “triangle of violence” by Johan Galtung is used here. Diaz presents the phenomenon of aggression in terms of structural, cultural and direct violence. Key words: Jorge Diaz’s The Sewers of Paradise, terrorism, religious intolerance, the Biblical myth of Cain and Abel, the violence triangle.